Experimental and Use-wear Examinations of Flint Knives: Reconstructing the Butchering Techniques of Prehistoric Lithuania - Rimkus, Tomas; Slah, Gvidas (Archaeologia Lituana, 2017)
The abundant quantity of flint blades with use-wear traces can be found within Lithuanian archaeological materials. These balades are frequently treated with various additional types of retouch techniques which provide more knowledge on the exploitation of those tools. An absence of organic material makes it extremely difficult to understand the real purpose of those artifacts. Suchlike flint blades, which typologically are considered as knives, are frequently found in Lithuania during excavations in the Late Neolithic–Early Bronze Age sites. Their exclusive technological specifics denote a particular function. In this paper, on the basis of flint knives from Lithuanian Late Neolithic and Early Bronze Age sites, we try to reconstruct the prehistoric technologies of animal butchering. In order to accomplish this task, both the experimental and use-wear methods were used. Our research results provided new insights on the use of flint knives and the effectiveness of metal tools in the animal butchering process.